2001
DOI: 10.1038/modpathol.3880312
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Diagnosis of Papillary Thyroid Carcinoma

Abstract: In thyroid, the diagnosis of papillary carcinoma (PC) is based on nuclear features; however, identification of these features is inconsistent and controversial. Proposed markers of PC include HBME-1, specific cytokeratins (CK) such as CK19, and ret, the latter reflecting a ret/PTC rearrangement. We applied immunohistochemical stains to determine the diagnostic accuracy of these three markers. . HBME-1 and ret were negative in all NH and FA; some of these exhibited focal CK19 reactivity in areas of degeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
221
0
8

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(245 citation statements)
references
References 12 publications
16
221
0
8
Order By: Relevance
“…The monoclonal antibody HBME1 was included for comparison because of its reported specificity for papillary thyroid carcinoma. [23][24][25] Our study shows that these proteins were not only expressed in papillary thyroid carcinomas but also in other follicular cell-derived thyroid carcinomas. Indeed, this relative lack of specificity for malignant tumors was very useful in differentiating all carcinomas from adenomas.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…The monoclonal antibody HBME1 was included for comparison because of its reported specificity for papillary thyroid carcinoma. [23][24][25] Our study shows that these proteins were not only expressed in papillary thyroid carcinomas but also in other follicular cell-derived thyroid carcinomas. Indeed, this relative lack of specificity for malignant tumors was very useful in differentiating all carcinomas from adenomas.…”
Section: Discussionmentioning
confidence: 60%
“…Several recent studies have reported HBME1 expression to be diagnostically useful in papillary thyroid carcinoma. 23,25 However, to the best of our knowledge, no single marker by itself is 100% sensitive for malignancy. By immunohistochemistry, ret/PTC and PPARg are reported in o70% of papillary and follicular thyroid carcinomas, respectively, while CD10 is expressed in follicular carcinoma and follicular variant of papillary carcinoma, but not in conventional papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, overall results obtained on fresh tissue, including our study, and cell blocks are rather concordant. The sensitivity of HBME-1 staining was excellent (490%) for classical PC (van Hoeven et al, 1998;Ito et al, 2005;Rossi et al, 2005), disappointing for PCFV, and poor (o65%) for follicular and undifferentiated cancers (Cheung et al, 2001;Mai et al, 2002;Ito et al, 2005;Prasad et al, 2005;Saggiorato et al, 2005). The reported specificity of HBME-1 staining ranged from 70% to more than 90% (Cheung et al, 2001;Prasad et al, 2005;Saggiorato et al, 2005).…”
Section: Discussionmentioning
confidence: 99%